Tales from the music therapy room : creative connections - Molyneux, Claire; Adamson, Robina, 1943- (Jessica Kingsley Publishers, 2018)
"Moving beyond progress reports, clinical assessments and practical goals, this book brings to life the reflective aspects of music therapy. The result of a collaboration between New Zealand music therapists, it invites the reader to share their encounters in the therapy room through a wide variety of writings, including short stories, poetry and personal reflections. The addition of poems by a music therapy client adds a rare and innovative dimension to this book. Grounded in clinical practice, each piece of writing starts from the lived experience in the therapy room and conveys something of the ineffable elements of music therapy. Thoughtful, touching and featuring beautiful illustrations, this book will appeal to anyone looking for a more personal account of music therapy practice, including practitioners, clients and students."--Publisher's description